Kafkasya’da islam medeniyeti : milletlerarası sempozyumu tebliğleri : Bakü-Azerbaycan, 9-11 Aralık 1998 = Islamic civilisation in Caucasia : proceedings of the international symposium : Baku-Azerbaijan, 9-11 December 1998 (İstanbul)
xl, 257 s.